Effect of Physical Workload, Nutritional Status with Work Fatigue on Work Productivity at PT. Semen Tonasa Pangkep Regency South Sulawesi - Rahmatullah, Rahmatullah; S Russeng, Syamsiar; Naiem, Furqaan; Thamrin, Yahya; Wahyu, Atjo; Palutturi, Sukri (Journal of Neonatal Surgery, 2025)
Background: Occupational fatigue is a problem that is often overlooked despite its serious impact on worker safety. It contributes 60% to workplace accidents. Prolonged high rates of fatigue can reduce cognitive function, and factors such as excessive workload, nutritional status exacerbate fatigue and have a negative impact on work productivity. The purpose of this study was to analyze the effect of workload, nutritional status with fatigue in workers on work productivity at PT Semen Tonasa located in Pangkep Regency, South Sulawesi. Methods: This analytical survey study with a cross-sectional design was conducted at PT Semen Tonasa, a cement factory in Pangkep Regency, South Sulawesi Indonesia, involving 144 workers. Data on workload, nutritional status, fatigue, and productivity were collected using questionnaires, body mass index and oximeter, and structured interviews. Path analysis was used to examine the direct and indirect effects of these variables on productivity. Results: The results showed that there was a significant positive effect of workload on work fatigue (2,496 > 1.96). there is a positive effect of nutritional status on work productivity (2,228 > 1.96), there is a positive effect of work fatigue on work productivity (3,938 > 1.96), Based on the intervening test, the indirect effect of workload on work productivity through work fatigue is -0.091 (negative effect). Conclusionsː In addition, there is a significant influence between workload, on work productivity through Work Fatigue and there is an insignificant influence of nutritional status on work productivity through Fatigue. It is expected that further research will be conducted on additional variables that can affect eye fatigue complaints in addition to the independent variables above.